Can you see me now? Video gatherings and social connectedness during the COVID-19 pandemic. Issue 1 (7th February 2022) - Marler, Will; Hargittai, Eszter; Nguyen, Minh Hao
Abstract: We surveyed American adults during the early months of the COVID-19 pandemic to examine who is more or less likely to use video chat for various types of social gatherings when in-person interactions are less available, and how such gatherings associate with feelings of social connectedness. We found that those with greater socioeconomic and digital privilege were more likely to engage in video gatherings, though participation related to lower social connectedness. Social gatherings over video chat may thus be the recourse for those already feeling disconnected when physically distanced; alternately, such gatherings may leave those who participate in them feeling less connected.